Immunobiological properties of medicinal product obtained on the basis of strains of Bifidobacteria and Lactobacilli - Khizhnyak, O (Annals of Mechnikov’s Institute, 2020)
The article treats issues of examination of safety of combined bacterial medicinal product on the basis of probiotic strains of bacteria belonging to two genera obtained by submerged mutual cultivation. During conducting experiments, it was found that the medicinal product causes no changes in blood hematological parameters of experimental animals, does not lead to their death, has no immunotoxic action, histological examination shows no deviations from the norm. In comparison with standard medicinal products, the proposed consortium of the said strains of bifidobacteria and lactobacilli does not differ by its safety from commercially available medicinal products “Bifidumbacterin” and “Lactobacterin” produced by PrJSC “Biofarma” but provides higher parameters of biological activity. There also was conducted examination of culture fluid activity after removal of proposed bacterial consortium. A high antibacterial activity of the sterile filtrate of culture fluid was found.